THE CONCEPT OF SMART CONTRACTS FROM THE LEGAL PERSPECTIVE - Kasprzyk, Karolina (Review of European and Comparative Law, 2018)
The purpose of article hereof is to introduce the significant characters of the smart contracts and certain ideas and proposals de lege ferenda on regulatory framework for smart contracts. Furthermore, present legislation with regard to the legal definition of the smart contract will be discussed from a comparative perspective. Particular note will be devoted to smart contracts in a relation to the contract law. Substantively, legal issues arising from the use of smart contracts, focussing upon actual and potential conflicts with established principles of contract law, will be introduced.